Clinical Characteristics of Ratborne Seoul Hantavirus Disease - Clement, Jan; LeDuc, James W.; McElhinney, Lorraine M.; Reynes, Jean-Marc; Van Ranst, Marc; Calisher, Charles H. (Emerging infectious diseases, 2019)
Although Seoul orthohantavirus is the only globally spread hantavirus pathogen, few confirmed human infections with this virus have been reported in Western countries, suggesting lower medical awareness of the milder, transient, and often chameleon-like symptoms of this zoonosis. We describe lesser known clinical and laboratory characteristics to help improve underreporting of this virus.